THE HARMONIZING MINE PLANNING IN THE EAST KALIMANTAN COKING COAL MINE: THE CHALLENGES AND IMPROVEMENTS - Ashabul Kahfi; Dwi P. Fransiskus; Wijanarko K. Adi; Ahmad Prayogi; Luqman S. Purwosasongko (Indonesian Mining Professionals Journal, 2023)
The coking coal mine at the research site is in the Pamaluan formation East Kalimantan. The condition of the mine has many complexities and challenges, such as natural slope condition (30º-35º), narrow pit area and low out pit dump capacity limited by land compensation issue, overburden material, geological structure, coal with very thin layers (<1 m) and consist multiple products in a layer, small number of strips and large number of blocks and high SR pit and SR balance in short range. In mine planning at the research location, many improvements need to be made so that all aspects, starting with mine planning and operations, can run smoothly and profits can be as expected. Some of the improvements that have been made at the mine such as build mine planning concepts, build fleet allocation rules, structural and stratigraphical geology modelling and improve drill & blast plan, implementation dynamic mine planning and optimize mining digital product. By implementing these improvements, significant positive impacts have been achieved, such as Consistently maintain mine planning compliance (accuracy) >97%, Maintain fleet productivity performance in range of 95% - 110%, Consistently achieving production targets >97%, Able to maintain SR balance by achieving weekly coal plan with the range of 94 - 103%, Achieving blasting performance results with a value of  >97% and Maintain work safety aspects with no accidents and loss time injury.